Clinical significance of novel biomarkers to predict the natural course of hepatitis B infection - Weikang Wu; Weikang Wu; Xiaojie Yuan; Weilu Zhang; Haowei Zhou; Xiangyu Kong; Zhen He; Ting Fu; Wenhua Zhang; Wenling Jia; Chunhui Liang; Haitao Tang; et al. (Frontiers Media S.A., 2022)
Background and aimChronic hepatitis B (CHB) can be divided into immune tolerance (IT), immune clearance (IC), hepatitis B e antigen (HBeAg)-negative inactive/quiescent carrier (ENQ), and HBeAg-negative hepatitis (ENH) phases. The conventional biomarkers used to distinguish these phases have limitations. We examined the clinical significance of hepatitis B virus (HBV) RNA and hepatitis B core-related antigen (HBcrAg) as novel biomarkers.MethodsOne hundred eighty-nine patients without treatment currently were categorized by CHB phase (IT = 46, IC = 45, ENQ = 49, ENH = 49). The associations of HBV RNA and HBcrAg with HBV DNA and alanine transaminase (ALT) were analyzed. The decision tree model was used to distinguish the four phases in the natural course of CHB.ResultsThe concentrations of HBV RNA and HBcrAg were highest in the IT and IC phases (P < 0.01). Serum HBV RNA was similar to HBcrAg in treatment-naïve patients. HBV RNA and HBcrAg correlated with HBV DNA in the HBeAg+ and HBeAg− status (HBV RNA: e+ r = 0.51, e− r = 0.62; HBcrAg: e+ r = 0.51, e− r = 0.71), but their association with HBV DNA differed among phases. The accuracy, sensitivity, and specificity of HBcrAg with ALT in distinguishing the CHB phases were 95.65%, 95.83%, and 95.55%, respectively.ConclusionSerum HBV RNA and HBcrAg may be useful to monitor CHB progression.